2021
DOI: 10.1097/md.0000000000027348
|View full text |Cite
|
Sign up to set email alerts
|

Rectal mixed adenoneuroendocrine carcinoma

Abstract: Rationale: Colorectal mixed neuroendocrine–nonneuroendocrine neoplasms constitute a rare group of gastrointestinal tumors composed by both neuroendocrine and nonneuroendocrine components. Nondiagnostic macroscopic features, specific histological features, and poor awareness of the disease are responsible for the underestimated incidence and conflicting data available. Due to lack of randomized clinical trials and validated clinical guidelines, diagnostic and therapeutic approach are based on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
(64 reference statements)
0
4
0
1
Order By: Relevance
“…Histologically, most cases are composed of adenocarcinoma and NEC. Rare cases in which the nonneuroendocrine component consisted of squamous cell carcinoma have also been noted[ 43 , 91 ]. If the neuroendocrine component consists of PDNEC, it is consistently observed in metastases.…”
Section: Organ-specific Clinicopathological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, most cases are composed of adenocarcinoma and NEC. Rare cases in which the nonneuroendocrine component consisted of squamous cell carcinoma have also been noted[ 43 , 91 ]. If the neuroendocrine component consists of PDNEC, it is consistently observed in metastases.…”
Section: Organ-specific Clinicopathological Findingsmentioning
confidence: 99%
“…In comparison, adenocarcinomas are observed in one-third of cases[ 47 ]. Such tumors show aggressive behavior and have poor prognosis (overall survival: 12.2 mo) according to the Ki67 proliferative index of the NEC component as well as the MSI status and stage[ 42 , 43 , 67 ]. Recently, a systematic review demonstrated that if the neuroendocrine component consists of NETs, it is unknown which component will be encountered in metastatic sites because of a higher grade, and the predominance of one component does not warrant their presence in metastatic sites[ 47 , 92 , 93 ].…”
Section: Organ-specific Clinicopathological Findingsmentioning
confidence: 99%
“…Kolorektaliniai MiNEN (mišrūs neuroendokrininiai ir neneuroendokrininiai navikai, turintys ne mažiau kaip 30 proc. kiekvieno iš komponentų) apibūdinami kaip reti, biologiškai agresyvūs, prastos prognozės navikai, dažnai diagnozuojami esant pažengusiai stadijai [1]. Dėl jų retumo didžiąją kolorektalinius MiNEN anali zuojančios mokslinės literatūros dalį sudaro klinikinių atvejų aprašymai ir nedideli retrospektyviniai tyrimai, o galimybę geriau suvokti šią patologiją ir apibendrinti informaciją sunkina besikeičianti terminologija bei tvirto mokslinio pagrindo neturinčios komponentų santykio ribos, todėl kol kas nėra visuotinai priimtų bend rų gairių aptariamos patologijos epidemiologijai, patogenezei, gydymui ir prognozei apibūdinti.…”
Section: įVadasunclassified
“…In 2019, malignant epithelial tumours of the colon and rectum were broadly of Digestive System tumours established that mixed neuroendocrine-nonneuroendocrine neoplasms were composed of at least 30% of each component and identified as "Mixed Adenoneuroendocrine Carcinomas (MANEC) [1].…”
Section: Introductionmentioning
confidence: 99%